Aerial Nitrogen Fluxes and Soil Nitrate in response to Fall-Applied Manure and Fertilizer Applications in Eastern South Dakota. (22nd September 2019) - Mehata, Mukesh; Cortus, Erin; Niraula, Suresh; Spiehs, Mindy J.; Darrington, Joseph; Chatterjee, Amitava; Rahman, Shafiqur; Parker, David B.
Abstract : Manure and inorganic fertilizer help to meet crop nitrogen demand by supplementing soil nitrogen (N). However, excessive N losses reduce soil fertility and crop yield and can impair water and air quality. The objectives of the research were to compare different forms of fall-applied N for (1) the change in soil nitrate (NO3 -N) over the growing season and (2) the aerial ammonia (NH3 ) and nitrous oxide (N2 O) fluxes during the fall and early growing season. Treatments included solid beef cattle manure with bedding (BM), solid beef cattle manure only (SM), urea (UO), and no fertilizer (NF). The two-year plot-scale study took place in Brookings County, South Dakota, under rain-fed conditions in a silty clay loam. Manure and urea were applied at equal plant-available N rates of 130 and 184 kg·N·ha −1 in Y1 and Y2, respectively, according to the South Dakota nutrient management planning process. The average total (i.e., 0–0.60 m soil depth) soil NO3 -N for Y1 (83 kg·ha −1 ) was significantly higher than Y2 (67 kg·ha −1 ), whereas surface (i.e., 0–0.15 m soil depth) soil NO3 -N was not significantly different between years. The average surface soil NO3 -N (33.5 kg·ha −1 ) and total soil NO3 -N (105.0 kg·ha −1 ) for UO were significantly higher than the remaining treatments (P < 0.05 ). Soil water NO3 -N concentrations, leaf-N, corn-grain-N, and yield measurements did not indicate any significant differences between treatments. Based on the two-year average, the highest NH3 -N flux occurred from the BM (3.4 g·ha −1 ·h −1 ); however, this flux was only significantly higher than NF (1.4 g·ha −1 ·h −1 ). The NH3 -N fluxes from UO (2.2 g·ha −1 ·h −1 ) and SM (1.7 g·ha −1 ·h −1 ) were similar to both BM and NF. The N2 O-N flux from UO (0.79 g·ha −1 ·h −1 ) was significantly greater than NF (0.25 g·ha −1 ·h −1 ), while BM- (0.49 g·ha −1 ·h −1 ) and SM-produced (0.33 g·ha −1 ·h −1 ) N2 O-N fluxes were not significantly different than neither UO nor NF. The three fall-applied N sources had similar aerial-N fluxes even though urea application resulted in significantly higher soil nitrate.